2020
DOI: 10.1088/1742-6596/1618/2/022065
|View full text |Cite
|
Sign up to set email alerts
|

Development of a digital twin of an onshore wind turbine using monitoring data

Abstract: The present paper has two main objectives: (1) to create a digital twin of an onshore wind turbine to provide to the owner of the wind farm a tool for continuous tracking of accumulated fatigue damage and evaluation of alternative operation strategies; (2) to perform the first tasks for the creation a reliable numerical of a floating wind turbine to simulate experimental data for the testing of monitoring tools on this type of wind turbines. A numerical model of an onshore wind turbine was created with FAST so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Therefore, digital twins are key enablers for the integration of renewable energy sources in smart grids, as they can predict, monitor, control, and diagnose energy supply [26]. Another application of digital twins is the monitorization of renewable energy generators as both physical damage and performance can be forecasted and modeled [27][28][29][30][31].…”
Section: The Effect Of Digitalization On the Renewable Energy Sectormentioning
confidence: 99%
“…Therefore, digital twins are key enablers for the integration of renewable energy sources in smart grids, as they can predict, monitor, control, and diagnose energy supply [26]. Another application of digital twins is the monitorization of renewable energy generators as both physical damage and performance can be forecasted and modeled [27][28][29][30][31].…”
Section: The Effect Of Digitalization On the Renewable Energy Sectormentioning
confidence: 99%
“…From Table 1, it can be concluded that most research focuses on turbines [24][25][26][27][28][29][30][31][32][33][34][35][36][37] and aeroengines [14,[45][46][47][48][49][50][51][52]. In terms of the application of turbines, research on wind turbines [30][31][32][33][34][35][36][37] accounts for a large proportion. In the aerospace field, some scholars have made efforts on aeroengines [45,47], while others have studied aircraft [14,[49][50][51][52].…”
Section: Overview On Life Cycle Of Turbomachinery With Digital Twinmentioning
confidence: 99%
“…From the perspective of the life cycle, the most numerous phases are monitoring [30][31][32][34][35][36][37]47] and manufacturing [27,[39][40][41]45,51]. In addition, there is currently a certain amount of research in the prediction [14,25,26,44,46] and design [27,38,42] phases, and many scholars are also concerned about the operation and maintenance [29,43,51] phase.…”
Section: Overview On Life Cycle Of Turbomachinery With Digital Twinmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent works, the concept of a modern DT was outlined for application to aircraft and aerospace structures [4,5], and further reviews on the application of DT technology can be found in [6,7]. Studies [8][9][10][11][12][13] have discussed the development of a digital twin of wind turbines, structural health monitoring using Supervisory Control And Data Acquisition (SCADA) data and autonomous Unmanned Aerial Vehicles (UAVs), damage detection using an AI-assisted image process, and alternative algorithms for wind turbines. These studies [8][9][10][11][12][13] have contributed to bringing more autonomy, automation, and optimization into wind turbines, which increasingly grow in size and complexity.…”
Section: Introduction To the Bigger Picturementioning
confidence: 99%